2003
DOI: 10.2337/diabetes.52.12.2914
|View full text |Cite
|
Sign up to set email alerts
|

Agouti Expression in Human Adipose Tissue

Abstract: It is well recognized that the agouti/melanocortin system is an important regulator of body weight homeostasis. Given that agouti is expressed in human adipose tissue and that the ectopic expression of agouti in adipose tissue results in moderately obese mice, the link between agouti expression in human adipose tissue and obesity/type 2 diabetes was investigated. Although there was no apparent relationship between agouti mRNA levels and BMI, agouti mRNA levels were significantly elevated in subjects with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…Such studies, together with a number of attempts to document the tissue distribution of melanocortin receptor mRNAs (36,38), have concluded that the MC2-R is not present in human adipocytes, and this lack of expression might be explained by the absence of an equivalent PPRE-like sequence in the proximal promoter of the human mc2-r. However, an analysis of the distal human promoter sequence revealed the presence of at least three putative PPRE-like elements, 2 and recent work using both human subcutaneous adipose tissue and human embryonic stem cell line capable of undergoing adipogenesis demonstrated the expression of mc2-r mRNA in the human adipocyte (39). Interestingly, the cell line used in this study is analogous to the 3T3-L1 cell line, being of embryonic mesenchymal origin.…”
Section: The Mmc2-r Promoter Responds To Rxr␣/ppar␥2 In Preadipocytesmentioning
confidence: 58%
“…Such studies, together with a number of attempts to document the tissue distribution of melanocortin receptor mRNAs (36,38), have concluded that the MC2-R is not present in human adipocytes, and this lack of expression might be explained by the absence of an equivalent PPRE-like sequence in the proximal promoter of the human mc2-r. However, an analysis of the distal human promoter sequence revealed the presence of at least three putative PPRE-like elements, 2 and recent work using both human subcutaneous adipose tissue and human embryonic stem cell line capable of undergoing adipogenesis demonstrated the expression of mc2-r mRNA in the human adipocyte (39). Interestingly, the cell line used in this study is analogous to the 3T3-L1 cell line, being of embryonic mesenchymal origin.…”
Section: The Mmc2-r Promoter Responds To Rxr␣/ppar␥2 In Preadipocytesmentioning
confidence: 58%
“…Subcutaneous adipose tissue biopsies were obtained from diabetic and nondiabetic subjects using a Bergstrom needle as previously described (22). RNA and DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…In ex vivo experiments with human adipocytes from obese subjects, high expression levels of MC1R, but only low levels of MC2R, have been detected (Smith et al 2003). Nevertheless, MC2R is expressed in human mesenchymal cells (MSC) during adipogenic induction (Smith et al 2003), suggesting that MC2R may have a role as a differentiating factor as in 3T3-L1 cells, but not in fully differentiated cells (Smith et al 2003, Betz et al 2012.…”
Section: Acth and Adipocyte Functionalitymentioning
confidence: 99%